Avaliação do potencial de compostos naturais (Argila, turfa e carvão) na remoção de chumbo e toxicidade de um efluente industrial - Tomasella, Richard Clayton [UNESP]; de Oliveira, Edson Gomes [UNESP]; de Angelis, Dejanira de Franceschi [UNESP]; Garcia, Marcelo Loureiro [UNESP] (FapUNIFESP (SciELO), 2015)
Advanced treatment methods using alternative adsorbent materials may replace or complement existing conventional treatments, aiding the removal of toxic substances coming from industrial processes. Spectrometry and biological tests (acute/chronic toxicity) aid the monitoring of industrial wastewater discharge, evaluating the effectiveness of these alternative systems of wastewater treatment. The study aimed to promote the reduction of lead (Pb) and toxicity concentration of an industrial effluent using the potential of natural compounds (clay and peat) and activated carbon (control) as adsorbents in batch tests. The activated carbon allowed a removal efficiency of 99.4% of Pb in the effluent (15 min.), and for others the removal occurred progressively up to 24 hours, resulting in removal efficiencies of 88.0% (Vale do Paraiba clay - VP), 73.6% (Ajapí clay - A) and 63.5% (peat). The acute toxicity was completely removed using activated carbon, as removal efficiencies higher than 50% were obtained using natural compounds. It was not observed significant toxic effect after the treatment with activated carbon and VP clay in relation to chronic toxicity. The results indicate the possibility of using VP clay as inexpensive commercial adsorbent in advanced treatment methods.
Evaluation of the potential of natural compounds (Clay, peat and activated carbon) for the removal of lead and toxicity of an industrial effluent
Keywords: Effluent polishing; Mineral adsorbent; Wastewater discharge